Gender and type of sports difference on perceived coaches' behavior during covid-19 pandemic: a case study of Federal Territory Sports Council Sukma 2021 athletes. / Wahidah Tumijan … [et al.] - Tumijan, Wahidah; Syed Mud Puad, Sharifah Maimunah; Ismail, Mazlan; Mohd Nor, Mohad Anizu; A Halim, Nur Asmidar; Hushin Amri, Hasnul Faizal; Mujail, Mazhan (Universiti Teknologi MARA, 2021)
The coach's actual conduct is thought to be influenced directly by his or her personal characteristics, such as age, gender, appearance, skill, and experience, as well as the demands of the situation. However, the coach's behavior set by both the organisational structure and the environment, and include factors including sport, team size or level, role variability, and playing conditions. This study aims to investigate on the different of perceived coaches’ behavior in terms of gender and type of sports among athletes in Federal Territory Sports Council, Sukan Malaysia (SUKMA) 2021 contingent. The research design of the study is quantitative research design. Total number of 468 samples was randomly selected from Federal Territory Sports Council, Sukan, Sukan Malaysia (SUKMA) 2021 contingent. The instrumentation used in this study is questionnaire which is Coaching Behavior Scale for Sport. The statistical analysis used is Independent T-test. The results showed significance result in the factor of negative personal rapport between gender and significance result showed in the technical skills between types of sports. In conclusion, depending on the pandemic scenario, all genders have a good view of coaches' actions, except for a negative personal rapport. Different types of sports exhibited similar perceptions of coaching behavior, except for technical skills, where individual athletes reported higher positive feedback than team athletes.